2014
DOI: 10.1177/0022429413520009
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Social Identity Development in Adolescent High School Choral Singers

Abstract: The purpose of this grounded theory study was to describe the process of adolescent choral singers’ social identity development within three midsized, midwestern high school mixed choirs. Forty-nine interviews were conducted with 36 different participants. Secondary data sources included memoing, observations, and interviews with the choir teachers. The data analysis revealed an eight-stage process beginning with the student’s choice to audition and remain involved to the final stage, a desire to give back to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 20 publications
10
50
0
Order By: Relevance
“…Finally, several ethnographic studies differing in their adopted theoretical perspectives on identity development demonstrated how mutual recognition among peers could be stimulated by engaging adolescents in learning activities that invite mutual encouragement (Carlone et al 2015;Tan and Calabrese Barton 2007) or by making adolescents aware of what they have in common (Hardee and Reyelt 2009;Jones and Deutsch 2013;Parker 2014;Tan and Calabrese Barton 2007). For example, in an art program studied by Hardee and Reyelt (2009), adolescents were asked to create art pieces.…”
Section: Supportive Classroom Climatementioning
confidence: 99%
“…Finally, several ethnographic studies differing in their adopted theoretical perspectives on identity development demonstrated how mutual recognition among peers could be stimulated by engaging adolescents in learning activities that invite mutual encouragement (Carlone et al 2015;Tan and Calabrese Barton 2007) or by making adolescents aware of what they have in common (Hardee and Reyelt 2009;Jones and Deutsch 2013;Parker 2014;Tan and Calabrese Barton 2007). For example, in an art program studied by Hardee and Reyelt (2009), adolescents were asked to create art pieces.…”
Section: Supportive Classroom Climatementioning
confidence: 99%
“…Singers can feel more secure if they have their fixed spatial positions where they feel supported within their vocal grouping (Bonshor, 2014). A sense of teamwork can be achieved through positive reinforcement of the factors that contribute to overall outcome, such as shared responsibility (Parker, 2014). Additionally, by heightening awareness of the musical outcome and praising performance success, individual and group efficacy can be improved (Wigfield and Eccles, 2000).…”
Section: Implications For Teachersmentioning
confidence: 99%
“…The purpose of this grounded theory study was to discover the process of social identity development in adolescent high school women's choir participants. With this study, I continued the line of grounded theory inquiry I began with auditioned adolescent mixed choir singers (see Parker, 2014). Similar to the previous inquiry, my research questions included how participants described the development of social identity within the context of the women's choir, what actions-interactions influenced social identity, what strategies participants used to develop social identity, what intervening conditions impeded social identity, and what consequences resulted from social identity development in women's choir.…”
mentioning
confidence: 99%